Local structure and hybridization states in Ba0.9Ca0.1Ti1-xZrxO3 ceramic compounds: Correlation with a normal or relaxor ferroelectric character - Mastelaro, Valmor Roberto; Favarim, Higor Rogerio; Mesquita, Alexandre [UNESP]; Michalowicz, Alain; Moscovici, Jacques; Eiras, José Antonio (Elsevier B.V., 2015)
This paper reports on a multi-edge X-ray absorption analysis to elucidate how the substitution of Ti4+ by Zr4+ ions acts on the local order structure and on the O 2p hybridization states of Ba0.9Ca0.1Ti1-xZrxO3 (BCZT) lead-free ceramic compounds, inducing a ferroelectric evolution from a normal to a relaxor character. Ti, Ba, Zr and 0 X-ray absorption spectra were measured to probe the local and electronic structure of BCZT samples that exhibit a normal (x < 0.18) or relaxor (x >= 0.18) ferroelectric character. X-ray absorption near edge structure results show that the local symmetry and distortion of TiO6, ZrO6 and BaO12 units are not significantly affected by the Ti/Zr ratio, the ferroelectric character or the long-range order symmetry. The assignment of the ab initio density of states associated with the O K-edge enabled a correlation between the decrease in the hybridization between O 2p and Ti 3d states and the ferroelectric character evolution of the BCZT samples. The hybridization states in the ferroelectric relaxor samples exhibit a more symmetric spatial configuration, as occurs with long-range symmetry.
Keywords: Ferroelectrics; Relaxors; Lead-free; Hybridization; XAS